THE ROLE OF PARENTS IN LEARNING HERITAGE LANGUAGE: A CASE STUDY OF ACEHNESE FAMILY - Idaryani Idaryani; Fidyati (Getsempena English Education Journal, 2022)
The old pattern of learning the heritage language has been disturbed because nowadays, some parents do no longer speak their heritage to their children as a mother tongue that consequently may result in a language shift among Acehnese children. The study aims to find out the role of parents in speaking Acehnese as a mother tongue to their children and how speaking Acehnese as a mother tongue for the children impacts on language maintenance and language shift among Acehnese children. This research is a case study that employed qualitative description. The data was collected based on interviews and observation. The informants of the study are six Acehnese people who live in Blang Puntuet village, one of the suburbs in Lhokseumawe city. The informants consist of three female parents and three Acehnese youths aged over 16 years old. The result of the study shows that from three families, one parent is actively speaking Acehnese to their children, one other parent is actively speaking Indonesian to their children, and the rest one is actively speaking Acehnese only to one of her three daughters. Therefore, the study indicates that once the old pattern is disturbed the ability of the children in speaking their heritage language is also disturbed because they are no longer actively speaking Acehnese in home in speech community.